Perancangan Sistem Aplikasi Web Pada Penjualan Nasi Uduk Dengan Metode Waterfall - Ahmad Fahmi Andrian; Marfel Crisly; Wahyudin (CV. Multi Kreasi Media, 2023)
Designing a web application system for selling nasi uduk with the waterfall method. Nasi uduk is a dish made of steamed white rice with coconut milk and diaron and seasoned with nutmeg, cinnamon, ginger, lemongrass leaves and pepper. This dish began to be made by residents of the island of Java around 1910-1924 and was popularized by the Dutch East Indies after the Nasi Uduk restaurant served orders and ate on the spot, or via telephone. So far, the Nasi Uduk restaurant has served orders and dined on the spot, or via telephone. For orders at the customer's place, you can go directly to the Nasi Uduk restaurant by buying/ordering the available food. For ordering at the customer's place, you can go directly to the Nasi Uduk restaurant by buying/ordering the available food. Therefore, we plan to build a sales-based information system. Online shop web with marketing strategy. With this online shop website, it is hoped that it can meet the business needs of the Nasi Uduk Restaurant.